2013
DOI: 10.5603/cj.2013.0019
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic challenge of artifactual electrocardiographic tachyarrhythmias

Abstract: Electrocardiographic artifacts may generate recordings mimicking supraventricular and ventricular tachyarrhythmias. This report describes the diagnostic challenge presented by Holter or loop recordings in two patients, one with pseudo-atrial flutter and the other with pseudo- -polymorphic ventricular tachycardia. (Cardiol J 2013; 20, 1: 106-109)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…The patient's humerus fracture was managed conservatively with coaptation splint immobilization and pain control. Artifacts mimicking atrial flutter and other arrhythmias have been described secondary to physiologic factors such as shivering from cold, Parkinsonian or benign essential tremor, hiccups, clonic contractions, poor electrode contact or other patient motion, or from non-physiologic factors such as electroconvulsive therapy, electromagnetic interference from electrical or electronic devices, or from devices such as left ventricular assist devices, continuous venovenous hemofiltration systems, implanted (deep thalamic, spinal cord) electro stimulators, transcutaneous electrical nerve stimulators, bladder stimulators, etc [1][2][3][4][5][6][7] . Pseudo-atrial flutter very similar to our patient's ECG has also been reported from a portable compact disc player placed close to the patient's right arm ECG lead [8] .…”
Section: Outcome and Follow-upmentioning
confidence: 99%
“…The patient's humerus fracture was managed conservatively with coaptation splint immobilization and pain control. Artifacts mimicking atrial flutter and other arrhythmias have been described secondary to physiologic factors such as shivering from cold, Parkinsonian or benign essential tremor, hiccups, clonic contractions, poor electrode contact or other patient motion, or from non-physiologic factors such as electroconvulsive therapy, electromagnetic interference from electrical or electronic devices, or from devices such as left ventricular assist devices, continuous venovenous hemofiltration systems, implanted (deep thalamic, spinal cord) electro stimulators, transcutaneous electrical nerve stimulators, bladder stimulators, etc [1][2][3][4][5][6][7] . Pseudo-atrial flutter very similar to our patient's ECG has also been reported from a portable compact disc player placed close to the patient's right arm ECG lead [8] .…”
Section: Outcome and Follow-upmentioning
confidence: 99%